Rare animals - Casterline, Linda (New York : Children's Press, 2003)
Introduces four endangered species--whooping cranes, elephants, monk seals, and polar bears--and describes what is being done to protect them and their habitats.
Born to fly free -- Caring for baby elephants -- Tracking seals underwater -- Travelers of the Arctic.
"A chapter book."
Includes bibliographical references (p. 46) and index.
4.3
3-6
Keywords: Rare animals -- Juvenile literature; Endangered species -- Juvenile literature; Rare animals; Endangered species; Wildlife conservation; Rare animals; Endangered species; Wildlife conservation